DETERMINASI FAKTOR INTERNAL–EKSTERNAL TERHADAP NILAI PERUSAHAAN TAMBANG DI INDONESIA - Anugerah Chresna Putra Sinulingga; Agustinus Winoto (Jurnal Trial Balance, 2025)
This study investigates the impact of liquidity, firm age, return on assets (ROA), debt-to-equity ratio (DER), firm size, and Gross Domestic Product (GDP) growth on firm value, measured by Tobin’s Q. The research focuses on mining companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2024 period. Panel data regression analysis is employed using EViews software, preceded by descriptive statistics, multicollinearity, autocorrelation, Chow, and Hausman tests to determine the most appropriate model. The findings reveal that only firm age has a negative and significant influence on firm value. This suggests that as companies become older, their market value relative to book value tends to decrease, reflecting a decline in investor perceptions of their growth prospects. In contrast, liquidity, ROA, DER, firm size, and GDP growth show no significant effect on Tobin’s Q. These results underscore the relevance of firm age as a key consideration in both investment decision-making and corporate management strategies.